Incident Hepatitis C Virus Infections in the Swiss HIV Cohort Study: Changes in Treatment Uptake and Outcomes Between 1991 and 2013. (19th February 2015) - Wandeler, Gilles; Schlauri, Marion; Jaquier, Marie-Eve; Rohrbach, Janine; Metzner, Karin J.; Fehr, Jan; Ambrosioni, Juan; Cavassini, Matthias; Stöckle, Marcel; Schmid, Patrick; Bernasconi, Enos; Keiser, Olivia; et al.
Abstract : In this large cohort of HIV-infected patients with an incident HCV infection, treatment uptake and outcomes improved in recent years. As a consequence, the proportion of patients with a detectable HCV viral load decreased significantly with time. Abstract: Background.  The hepatitis C virus (HCV) epidemic is evolving rapidly in patients infected with human immunodeficiency virus (HIV). We aimed to describe changes in treatment uptake and outcomes of incident HCV infections before and after 2006, the time-point at which major changes in HCV epidemic became apparent. Methods.  We included all adults with an incident HCV infection before June 2012 in the Swiss HIV Cohort Study, a prospective nationwide representative cohort of individuals infected with HIV. We assessed the following outcomes by time period: the proportion of patients starting an HCV therapy, the proportion of treated patients achieving a sustained virological response (SVR), and the proportion of patients with persistent HCV infection during follow-up. Results.  Of 193 patients with an HCV seroconversion, 106 were diagnosed before and 87 after January 2006. The proportion of men who have sex with men increased from 24% before to 85% after 2006 ( P < .001). Hepatitis C virus treatment uptake increased from 33% before 2006 to 77% after 2006 ( P < .001). Treatment was started during early infection in 22% of patients before and 91% after 2006 ( P < .001). An SVR was achieved in 78% and 29% ( P = .01) of patients treated during early and chronic HCV infection. The probability of having a detectable viral load 5 years after diagnosis was 0.67 (95% confidence interval [CI], 0.58–0.77) in the group diagnosed before 2006 and 0.24 (95% CI, 0.16–0.35) in the other group ( P < .001). Conclusions.  In recent years, increased uptake and earlier initiation of HCV therapy among patients with incident infections significantly reduced the proportion of patients with replicating HCV.